Research and Performance Test of New Full-Length Anchorage Material. (4th June 2021) - Huang, Shunjie; Meng, Xiangrui; Zhao, Guangming; Li, Yingming; Cheng, Xiang; Xu, Wensong; Liu, Gang
Abstract : It is difficult to support roadway with anchor cable in view of impact tendency in impinging liability roadway; a new material of inorganic and high-performance full-length anchoring material for anchoring cable is developed by adding several modifiers with ultrafine cement as the main material. The purpose is to improve the mechanical properties and durability of cement-based materials, improve the coordination of anchor cable support system, and ensure the stability of surrounding rock of mining roadway. The new full-length anchoring material is developed by optimizing the proportion of different components of the material, and the mechanical properties of the new material were studied. The anchoring force of resin anchoring agent, ordinary Portland cement, blank ultrafine cement, and new full-length anchoring material are tested. Based on SEM microscopic characterization, the fracture types and failure characteristics of resin anchoring agent and full-length anchoring material are researched. The results show that the optimal content of each component of the new inorganic high-performance full-length anchorage material is as follows: the content of component A is 15%, the content of component B is 3%, the content of component C is 0.2%, the content of component D is 1%, and the content of component E is 1%; the tensile test shows that the full-length anchoring material has good bonding property, high anchoring strength, strong stability, and good rock coupling. SEM microstructure and morphology analysis have showed that the new anchorage materials can fully hydrate each other, resulting in a relatively dense stone body. The new full-length anchoring material can effectively improve the anchoring force and improve the stability of the anchor cable and has significant performance advantages and good engineering applicability, and it has the advantages of lower cost and safer to use. The new material is a very good supporting material for roadway.